2020
DOI: 10.1590/2175-8239-jbn-2019-0187
|View full text |Cite
|
Sign up to set email alerts
|

Non-recovery of renal function is a strong independent risk factor associated with mortality in AKI patients

Abstract: Introduction: Acute kidney injury (AKI) is a recurrent complication in the intensive care unit (ICU) and is associated with negative outcomes. Objective: To investigate factors associated with mortality in critically ill AKI patients in a South Brazilian ICU. Methods: The study was observational retrospective involving AKI patients admitted to the ICU between January 2011 and December 2016 of at least 18 years old upon admission and who remained in the ICU at least 48 hours. Comparisons between selected char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Different aspects influence incidence rates, which can still be affected by geographic aspects. While an international multicenter study showed a global AKI prevalence rate of 44.6% in patients in critical care units, specifically in South America a reduction was identified, 12.7% (7) , but in another study this variation reached 20% to 40% of involvement (8) . However, despite advances in diagnosis and therapies, mortality has changed little in recent years, affecting 40% to 80% of patients admitted to ICUs, which emphasizes the need to implement tools to the earlier identification of acute kidney injury (9) .…”
Section: Introductionmentioning
confidence: 91%
“…Different aspects influence incidence rates, which can still be affected by geographic aspects. While an international multicenter study showed a global AKI prevalence rate of 44.6% in patients in critical care units, specifically in South America a reduction was identified, 12.7% (7) , but in another study this variation reached 20% to 40% of involvement (8) . However, despite advances in diagnosis and therapies, mortality has changed little in recent years, affecting 40% to 80% of patients admitted to ICUs, which emphasizes the need to implement tools to the earlier identification of acute kidney injury (9) .…”
Section: Introductionmentioning
confidence: 91%
“…Acute kidney injury (AKI) is a clinical syndrome of varied etiology characterized by a sudden decrease in kidney function, accumulation of waste metabolites, water-mineral imbalance, and systemic symptoms. It is a common problem in intensive care medicine since a moderate AKI increases the risk of death by approximately five times 1 , 2 .…”
Section: Introductionmentioning
confidence: 99%